Penerapan Pendidikan Jasmani Berbasis Karakter melalui Permainan Gobak Sodor dan Bentengan pada Siswa Kelas V di SDN Pangarangan III Sumenep - Elfarita, Nadia; Suparto, Achmad; Basri, Mohammad Hasan (MAN Insan Cendekia Jambi, 2025)
This study aims to describe the implementation of traditional games Gobak Sodor and Bentengan in physical education as a medium for character learning for fifth grade students at SDN Pangarangan III Sumenep. The research method used is a qualitative approach with a descriptive nature, where data is collected through interviews with the principal, physical education teachers, and students, as well as direct observation during learning activities. The results of the study indicate that the implementation of traditional games in physical education contributes to strengthening students' character, especially in aspects of cooperation, sportsmanship, leadership, and responsibility. The Gobak Sodor game emphasizes team coordination and defensive strategies, while Bentengan trains courage and the ability to make decisions quickly. Although there are obstacles such as limited playing fields and students' understanding of the rules of the game, teachers are able to overcome these challenges by modifying the rules and strategies of the game. In addition, students show high enthusiasm for the implementation of this game in learning, because traditional games are considered more interesting and fun than conventional physical activities. Therefore, traditional games can be used as an alternative learning method in physical education that not only improves students' physical fitness but also strengthens important character values ​​in life.